Analisis Pengaruh Strategi Lini Produk terhadap Perilaku Konsumtif Mahasiswa Polban pada Transaksi Online - Simanjuntak, Dina Yosephine Valentine; Chaniago, Harmon (International Journal Administration, Business & Organization, 2023)
This study analyzes the effect of product line strategy on consumptive behaviour. This research case study was conducted on active POLBAN students for the 2019-2022 class. The method used is a quantitative descriptive method where primary data is the source of this research. Primary data was collected from G-Forms questionnaire distribution data distributed to 110 respondents. Primary data has been obtained and analyzed using a data processing validity test, reliability test, normality test, hypothesis test, and correlation analysis. Data analysis was obtained by simple linear regression. This data processing was processed using SPSS 26 software. The results of this study indicate that the product line strategy has a 5.55% influence on consumptive behaviour in online transactions (e-commerce). The magnitude of the proportion is a positive and significant influence. The larger the strategic product line, the higher the consumptive behaviour.